Montmorillonite-alginate beads: Natural mineral and biopolymers based sorbent of paraquat herbicides - Etcheverry, Mariana (2017)
Beads of alginate montmorillonite have been used for the first time as sorbent of the cationic pesticide paraquat (PQ). They are a green material because they are formed by a biopolymer and a clay mineral, and because they allow using an energy efficient process to separate the beads after PQ adsorption. The general characterization of the beads, with montmorillonite contents ranging from 0% to 70%, has been carried out by elemental composition, FTIR and thermal analysis. The shape, external morphology and internal structure of the beads were examined by SEM. Wet beads were also observed with a digital camera. PQ adsorption was studied with adsorption isotherms from aqueous solutions, and maximum adsorption capacities (Qmax) were 0.093, 0.146, 0.187 and 0.278 mmol g−1 for montmorillonite contents of 0, 5, 30 and 70%, respectively. Qmax varied linearly with the clay content. The results show that montmorillonite is practically the only PQ sorbent, with alginate acting mainly as support of the clay particles, but playing a very important role allowing an effortless handling of the material and the adsorbed pollutant.